2002
DOI: 10.1016/s0002-9440(10)64878-x
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Functional Interleukin-3 Receptors on Hodgkin and Reed-Sternberg Cells

Abstract: The human interleukin-3 receptor (IL-3R) is a heterodimeric complex consisting of an IL-3-specific alpha chain (IL-3Ralpha) and a common beta chain (beta(c)), this latter shared with the receptors for granulocyte-macrophage colony-stimulating factor and IL-5. Despite extensive research on cytokine circuitries regulating proliferation and survival of tumor cells in Hodgkin's disease (HD) the functional expression of IL-3Rs in this pathobiological entity has not yet been investigated. In the present study, we de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
58
1
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 58 publications
(66 citation statements)
references
References 65 publications
(82 reference statements)
6
58
1
1
Order By: Relevance
“…27 Similarly, IL-3 and IL-9 are functionally expressed in HRS cells and promote their proliferation. 26 Whether one of these secreted factors mediates its effects through activation of alternative NF-kB signaling in HRS cells, and whether aberrant Notch signaling might even control its expression requires further investigations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…27 Similarly, IL-3 and IL-9 are functionally expressed in HRS cells and promote their proliferation. 26 Whether one of these secreted factors mediates its effects through activation of alternative NF-kB signaling in HRS cells, and whether aberrant Notch signaling might even control its expression requires further investigations.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that HRS cells abundantly secrete soluble factors, such as cytokines and chemokines, and that they are involved in forming the particular microenvironment in cHL, and trigger HRS cell proliferation and survival. 14,[25][26][27] We incubated HRS cells with fresh or conditioned medium of untreated L540cy, L1236, KM-H2 and L428 cells, and simultaneously added GSI XII for 24 h. NF-kB p52 levels, which are indicative for alternative NF-kB signaling, remained stable in L540cy cells upon stimulation of cells with conditioned medium (Figure 5a, upper panel). Accordingly, conditioned medium efficiently reversed the loss of cell viability of GSI-treated HRS cells (Figure 5a, lower panel and Supplementary Figures S2A and B).…”
Section: Stimulation Of Alternative Nf-kb Signaling Rescues Hrs Cellsmentioning
confidence: 99%
“…Effects on the Th1/Th2 balance have been observed in some animal models of allergy [184]; however not all strains stimulated Th1 immunity [185,186]. Nonetheless, stimulation of Th1 immunity has been reported in clinical trials [187][188][189][190][191] and clinical efficacy has been demonstrated in adults, children and infants for diseases including IBS and IBD [192,193], see Figure 4. …”
Section: Regulation Of Immune Responsesmentioning
confidence: 99%
“…Cell lysates from leukemia/lymphoma T-cell lines were prepared as described (33). Equal amounts of protein (50 g) were subjected to10% SDS-PAGE.…”
Section: Isolation and Characterization Of Cd26mentioning
confidence: 99%
“…Clonogenic growth of leukemia/lymphoma T-cell lines, H9 T-cell clones, and primary leukemic T cells was assayed as described previously (2,33). Briefly, 2.0 ϫ 10 5 /ml purified tumor T cells or 5.0 ϫ 10 3 /ml T-cell lines, were suspended in 1 ml of IMDM …”
Section: Colony Assay and [ 3 H]thymidinementioning
confidence: 99%